2013
DOI: 10.1002/bdra.23149
|View full text |Cite
|
Sign up to set email alerts
|

Periostin downregulation is an early marker of inhibited neonatal murine lung alveolar septation

Abstract: BACKGROUND Extreme preterm birth exposes the saccular lung to multiple teratogens, which ultimately retard alveolar development. Specifically, therapeutic high level oxygen supplementation adversely affects the premature lungs and results in blunted alveolarization. Prolonged hyperoxic lung injury has previously been shown to upregulate the matricellular protein Periostin (Postn) and stimulate ectopic accumulation of alpha smooth muscle actin (αSMA) myofibroblasts. Therapies that promote lung septation are lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…6K, Data in Brief Table 4). Persistence and overabundance of myofibroblasts in the alveolar interstitium, because of premature birth or perinatal hyperoxia exposure, is found in association with arrested alveolar septation in bronchopulmonary dysplasia (BPD) (Ahlfeld et al, 2013; Bozyk et al, 2012; Toti et al, 1997). Further analysis of Profile #18, which contains 66 genes that are uniquely upregulated on PN7, in combination with gene expression studies from BPD samples and other septation defects will provide valuable insight into the regulatory networks that result in fibroblast differentiation to smooth muscle cells or transient myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…6K, Data in Brief Table 4). Persistence and overabundance of myofibroblasts in the alveolar interstitium, because of premature birth or perinatal hyperoxia exposure, is found in association with arrested alveolar septation in bronchopulmonary dysplasia (BPD) (Ahlfeld et al, 2013; Bozyk et al, 2012; Toti et al, 1997). Further analysis of Profile #18, which contains 66 genes that are uniquely upregulated on PN7, in combination with gene expression studies from BPD samples and other septation defects will provide valuable insight into the regulatory networks that result in fibroblast differentiation to smooth muscle cells or transient myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, investigators have shown that POSTN is widely expressed by mesenchymal cells during the saccular stage of lung development and is coincident with the accumulation of a-SMA myofibroblasts. 33 Studies have shown that POSTN may play an important role in normal alveolar septation and can function as a ligand for a v b 3 and a v b 5 integrins, thereby having pleiotropic effects in supporting adhesion and migration of epithelial cells. 34,35 Others have demonstrated that POSTN potentiates the effects of the TGF-b family of peptides, which are known to exert inhibitory effects on lung epithelial cell proliferation and to cause epithelial-tomesenchymal transition during terminal bud morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…After determination of DF CO , lungs were immediately inflation fixed. The left lung volume was determined by fluid displacement and then processed and stained for determination of mean linear intercept (Lm) and alveolar surface area (estimated as 4V/Lm), as previously described (17,22).…”
Section: Methodsmentioning
confidence: 99%